2022
DOI: 10.1210/clinem/dgac636
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons Between Different Anti-osteoporosis Medications on Postfracture Mortality: A Population-Based Study

Abstract: Context Osteoporosis is becoming a global epidemic in aging societies. Anti-osteoporotic medications can prevent fractures, and their pleiotropic effect on mortality is interesting but not well compared among each other. Objectives To provide real-world evidence on the pleiotropic effect of different anti-osteoporotic medications on all-cause mortality, stratified by fracture site, sex, and age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…The HORIZON (Health Outcomes and Reduced Incidence with Zoledronic Acid Once Yearly) Recurrent Fracture Trial originally demonstrated a 28% reduction in mortality in patients with a hip fracture who were randomized to receive zoledronic acid 14 . Current articles by Wu et al 15 and Tai et al 16 have evaluated the impact of various anti-osteoporotic drugs on all-cause mortality after hip fractures in a nationwide population study in Taiwan. In this large study, 45,266 patients with an osteoporotic hip fracture who were subsequently treated with various anti-osteoporotic drugs were identified.…”
Section: Osteoporosis Drug Therapymentioning
confidence: 99%
“…The HORIZON (Health Outcomes and Reduced Incidence with Zoledronic Acid Once Yearly) Recurrent Fracture Trial originally demonstrated a 28% reduction in mortality in patients with a hip fracture who were randomized to receive zoledronic acid 14 . Current articles by Wu et al 15 and Tai et al 16 have evaluated the impact of various anti-osteoporotic drugs on all-cause mortality after hip fractures in a nationwide population study in Taiwan. In this large study, 45,266 patients with an osteoporotic hip fracture who were subsequently treated with various anti-osteoporotic drugs were identified.…”
Section: Osteoporosis Drug Therapymentioning
confidence: 99%
“…A number of studies (but not all [106]) concluded that use of antiresorptive medications improved survival [30,[107][108][109][110][111][112][113][114][115][116]. Our study does not have sufcient statistical power to reach the same conclusions.…”
Section: Ckd and Hospital Outcomesmentioning
confidence: 60%
“…Immediate strategies should also consider pharmacologic treatments to reduce imminent fracture risk. 31 , 32 , 34 Recently, a large population-based observational study has shown mortality benefits for various types of treatments 52 , 53 ; albeit, not without methodological limitations inherent to observational study design 54 and with adequately designed randomized trials examining all-cause mortality being scarce. 55 An absence of prior antiosteoporosis treatment was, however, observed to be associated with increased postfracture mortality, 12 and a clinical pathway focusing on improving post-fracture treatment rates, known as fracture liaison service, has also been shown to reduce mortality.…”
Section: Discussionmentioning
confidence: 99%